A System Dynamics Approach to Model Photosynthesis at Leaf Level Under Fluctuating Light - Salvatori, Nicole; Carteni, Fabrizio; Giannino, Francesco; Alberti, Giorgio; Mazzoleni, Stefano; Peressotti, Alessandro (Frontiers in Plant Science, 2022)
Photosynthesis has been mainly studied under steady state conditions even though this assumption results inadequate for assessing the biochemical responses to rapid variations occurring in natural environments. The combination of mathematical models with available data may enhance the understanding of the dynamic responses of plants to fluctuating environments and can be used to make predictions on how photosynthesis would respond to non-steady state conditions. Here we present a leaf level System Dynamics photosynthesis model based and validated on an experiment performed on two soybean varieties, the wildtype Eiko and the chlorophyll deficient mutant Minngold, grown in constant and fluctuating light conditions. This mutant is known to have similar steady-state photosynthesis compared to the green wildtype, but it is found to have less biomass at harvest. It has been hypothesized that this might be due to an unoptimized response to non-steady state conditions, therefore this mutant seems appropriate to investigate dynamic photosynthesis. The model explained well the photosynthetic responses of these two varieties to fluctuating and constant light conditions and allowed to make relevant conclusions on the different dynamic responses of the two varieties. Deviations between data and model simulations are mostly evident in the NPQ dynamics due to the oversimplified combination of PsbS- and zeaxanthin- dependent kinetics, failing in finely capturing the NPQ responses at different timescales. Nevertheless, due to its simplicity, the model can provide the basis of an upscaled dynamic model at plant level.